Cause Analysis of Budget Deficit in BPJS for Health - Nelisya Putri; Aqwa Naser Daulay; Kamila Kamila; Ahsan Putra Hafiz (Journal of Management and Business Innovations, 2020)
This study aims to determine the factors causing the budget deficit of the Social Security Administering Body (BPJS) for Health. This research is important to do in order to find out the root cause of the deficit of the Social Security Administering Body (BPJS) and find a solution so that the sustainability of the BPJS can be ascertained. This study focuses on the phenomena that occur in BPJS for Health. The purpose of this study is to examine the root causes of the BPJS budget deficit and the role of the government in overcoming the BPJS health deficit. This type of research is descriptive qualitative. In collecting research data using interview techniques and by using informants as a source of information and Annual reports as the object used. The results of this study indicate that the factors causing the BPJS Health budget deficit are the amount of contributions that are not sufficient to finance service expenditures, especially since the burden of health services for catastrophic diseases is very high and continues to increase. The financial management of BPJS for Health is used entirely for program development as much as possible and for the benefit of the participants. Then there have been many policy options undertaken by the government to overcome the BPJS health budget deficit, namely by increasing contributions. Researchers also see that the low level of public awareness of the importance of health insurance and a wrong understanding of the principles of social insurance as well as providing socialization to the community, especially instilling the principle of mutual cooperation in all Indonesians.Keywords: Budget, BPJS for health, deficit